Cellular responses to in vitro exposures to β-blocking pharmaceuticals in hard clams and Eastern oysters. (November 2018) - Khan, Bushra; Burgess, Robert M.; Fogg, Sandra A.; Cantwell, Mark G.; Katz, David R.; Ho, Kay T.
Abstract: Increased consumption and improper disposal of prescription medication, such as beta (β)-blockers, contribute to their introduction into waterways and may pose threats to non-target aquatic organisms. There has been rising concern about the impacts of these prescription drugs on coastal ecosystems, especially because wastewater treatment plants are not designed to eliminate them from the discharge. Few studies have characterized the sublethal effects of β-blocker exposures in marine invertebrates. The overall aim of our research is to identify cellular responses of two commercially important filter-feeding marine bivalves, hard clams ( Mercenaria mercenaria ) and Eastern oysters ( Crassostrea virginica ), upon exposures to two β-blocker drugs, propranolol and metoprolol. In vitro exposures with bivalve digestive gland and gill tissues were conducted where tissues were separately exposed to each drug for 24 h. Tissue samples were analyzed for cellular damage (lysosomal membrane destabilization and lipid peroxidation), total antioxidant capacity, and glutathione-s-transferase activity. Elevated damage and changes in enzyme activities were noted in the exposed tissues at environmentally relevant concentrations. Differences in species and tissue sensitivities and responses to exposures were also observed. These studies enhance our understanding of the potential impacts of prescription medication on coastal organisms. Additionally, this work demonstrates that filter-feeders may serve as good model organisms to examine the effects of unintended environmental exposures to β-blockers. These studies are part of our ongoing work aimed at evaluation of sublethal biomarkers of pharmaceutical exposures and identification of key events that can contribute to the development of adverse outcome pathways (AOPs). Highlights: β-blocker exposures can induce lysosomal damage in marine bivalves. Changes in activities of glutathione-s-transferase were noted in exposed bivalves. Digestive gland tissues are more sensitive to β-blocker exposures than gills. Species-specific differences were noted in responses to β-blocker exposures.